2014
DOI: 10.1186/1472-6920-14-145
|View full text |Cite
|
Sign up to set email alerts
|

Internal consistency of the readiness for interprofessional learning scale in German health care students and professionals

Abstract: BackgroundThe implementation of a bachelor degree in “Interprofessional Health Care” at the University of Heidelberg, Germany has fostered the need to evaluate the impact of this innovative programme. The Readiness for Interprofessional Learning Scale (RIPLS) was developed by Parsell and Bligh (1999) to assess student’s attitudes towards interprofessional education. The RIPLS consists of 19 items and four subscales were identified by McFadyen (J Interprof Care19:595–603, 2005): “teamwork and collaboration”, “n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 38 publications
4
57
0
4
Order By: Relevance
“…The index values obtained in the present study were higher than those obtained from other RIPLS adaptation studies; as a result, the structure of the tested Turkish version of the scale is thought to be consistent. In the present study, after CFA, similar values were obtained with the structure suggested and confirmed by Parsell and Bligh 21 and with those tested and confirmed by Lauffs et al 23 and Mahler et al 26 With the exception of Cloutier et al, 25 the team and collaboration sub-scale in all studies was consistent with the results of Parsell and Bligh. 21 The lowest degree of reliability was obtained in the roles and responsibilities sub-scale in the present study; similarly, Parsell's study also yielded low levels of reliability in the same sub-scale.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The index values obtained in the present study were higher than those obtained from other RIPLS adaptation studies; as a result, the structure of the tested Turkish version of the scale is thought to be consistent. In the present study, after CFA, similar values were obtained with the structure suggested and confirmed by Parsell and Bligh 21 and with those tested and confirmed by Lauffs et al 23 and Mahler et al 26 With the exception of Cloutier et al, 25 the team and collaboration sub-scale in all studies was consistent with the results of Parsell and Bligh. 21 The lowest degree of reliability was obtained in the roles and responsibilities sub-scale in the present study; similarly, Parsell's study also yielded low levels of reliability in the same sub-scale.…”
Section: Discussionsupporting
confidence: 92%
“…Different studies show inconsistent results for the professional identity sub-scale. [21][22][23]26 The most outstanding results among the adaptation studies were obtained by Cloutier et al 25 The 18 th and 19 th items in that study were excluded, and the remaining items were associated with different, re-named factors. The titles of the sub-scales and their associations with the factors are different in the Japanese 24 and the French 25 adaptations of the original scale; when those adaptation studies were investigated, it was noted that an approach that considered cultural differences and subject fields was necessary to obtain similar results to the original scale.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fragebogens "Readiness for interprofessional Learning Scale" (RIPLS) verwendet (Parsell & Bligh, 1999; deutsche Version RIPLS-D von Mahler et al, 2014 Auf Grund der in der Literatur mehrfach nachgewiesenen ungenügenden internen Konsistenz der Subskalen 2 und 3 des Instrumentes wurden diese in der vorliegenden Untersuchung nicht berücksichtigt. Alle Items sind als Aussagen formuliert, die auf einer fünfstufigen Skala von 1 = trifft gar nicht zu" bis 5 = "trifft sehr zu" beantwortet werden können.…”
Section: Für Die Erfassung Der Bereitschaft Zur Interprofessionellen unclassified
“…Die Spannweite der Subskala beträgt 9 bis 45 Punkte. Die interne Konsistenz der Subskala 1 ist in der untersuchten Stichprobe gut (Cronbachs Alpha 0.80) und vergleichbar mit den Resultaten anderer Studien (Mahler et al, 2014;Parsell & Bligh, 1999 …”
Section: Für Die Erfassung Der Bereitschaft Zur Interprofessionellen unclassified